Formulação de grautes leves para a cimentação de poços de petróleo onshore - Gouveia, Priscila Siqueira de (2012)
Grautes are dry mixes with hydraulic characteristics widely used in construction. This material comprises cement, mineral additives and dosed in accordance with the desired properties. The use of grautes in cementing oil wells potentially increases the precision in the composition of the mixture, since it is requires only the addition of the mixing water before its pumping. Such benefit may be availed in cementing wells since the formulations grautes meet the temperature and pressure characteristics typical of wells. The objective of this study is to evaluate the effect of adding different percentages of industrial minerals properties of light grautes for onshore oil wells. For the formulation of the employees were grautes light industrial minerals and waste minerals abundant in the Northeast, in addiction to Portland cement and chemical additives Special class. Grautes were formulated with densities between 1.55 g/cm3 (13.0 lb/gal) and 1.68 g/cm3 (14 lb/gal). Tests results showed that grautes with higher density in the range studied meet the specifications for cementation of shallow wells onshore. The compositions lighter can also be adjusted for applying the material in the cementation of oil wells